Educação de Jovens e Adultos (EJA): Um estudo das Diretrizes Operacionais para a Educação de Jovens e Adultos (Resolução nº° 1, de 28 de maio de 2021) - Santos, Letícia De Oliveira Dos (2024)
The general objective of this dissertation was to understand the processes involved in the discussion and promulgation of Resolution No. 1, of May 28th, 2021, which established the Operational Guidelines for Youth and Adult Education (EJA), especially with regard to aspects related to Distance Education (EAD), taking into account the role of public authorities in making the right to education effective for young people, adults and the elderly. Predominantly qualitative in nature, it considers documentary research as the main technique for analyzing the research source: Resolution No. 1, of May 28, 2021, promulgated during the administration of former president Jair Bolsonaro. Given the complex and controversial nature of educational policy and studies in the field of EJA, Stephen Ball and Richard Bowe's "policy cycle" approach as presented by Mainardes (2006), was taken as a reference for analyzing the aforementioned documentary source. Based on the dialogue with the relevant literature, the macro-political processes, continuities and discontinuities of the policies that impacted the production of the source in question were analyzed. It could be noticed that Resolution No. 01 of 2021 presents a positive and technicist view of distance education, which seems to disregard the specificities of the EJA subjects pointed out by studies in the field. In addition, its text dialogues superficially and in a distorted way with the idea of Lifelong Learning. Such aspects are in addition to local and international trends, influences and discourses that are aligned with the administration of Jair Messias Bolsonaro, president of Brazil at the time of the promulgation of Resolution No. 01 of 2021; an administration marked by the unaccountability of the state, ultraconservative politics and culture and by the strengthening of a neoliberal agenda.